Sperm Quality Assessment of White Shrimp (Litopenaeus Vannamei) Broodstock using Comet Assay - Duangjai, Ekachai; Umyoo, Pokpong; Meunpol, Oraporn; Puanglarp, Narongsak (Trends in Sciences, 2023)
The quality of sperms is considered one of the factors determining fertilization success of white shrimp, Litopenaeus vannamei. Generally, conventional methods such as sperm count and viability are used for determining sperm quality. Occasionally, the fertilization rate does not correlate with what conventional parameters indicate. Presently, it has become increasingly evident that sperm DNA damage is a potential cause of an unexplained fertilization incompetence of the sperm. Therefore, the present study aimed to determine the feasible application of the comet assay for measuring sperm quality from different male broodstock and to analyze the correlation between sperm DNA integrity and fertilization efficacy of the shrimp. Male and female shrimp sampled from 4 different broodstock ponds were mated in experimental tanks (n = 5). Sperm were collected and subjected to alkaline comet assay. Sperm count, sperm viability, and Gonadosomatic index(GSI) were analyzed for comparison. Viability of the obtained nauplii were recorded and used as larvae production efficiency. The results revealed that nauplius numbers were significantly different among treatments (6.78±1.61×104, 12.18±1.17×104, 16.76±0.97×104 and 21.38±1.14×104 cells/spawn in treatment 1, 2, 3 and 4, respectively), indicating the different fertilization rate between treatments. The average body weights, lengths, and GSIs of broodstock were not significantly different, indicating that the morphological factors were not major causes of the different nauplii production among treatments. The results of comet measurements clearly showed that the levels of comet parameters correlated with the numbers of nauplii obtained from each treatment while the conventional sperm analyses were unable to detect the different quality of the sperm among treatments. This indicates that the degree of sperm DNA damage correlates with the fertilization rate of the shrimp and can be used as a sensitive indicator for determining sperm quality of broodstock shrimp. HIGHLIGHTS Sperm DNA damage is one of the potential causes of low fertilization rate in L. vannamei captive breeding Comet assay is used to assess the degree of DNA damage in a single cell such as shrimp sperm cell using electrophoresis technique Comet assay is more sensitive to detect the sperm integrity among individual L. vannamei broodstock when compared to morphological methods Sperm DNA damage can be used as a sensitive indicator for determining the sperm quality of L. Vannamei GRAPHICAL ABSTRACT